Brine-Induced Tribocorrosion Accelerates Wear on Stainless Steel: Implications for Mars Exploration. (28th December 2021) - Martín‐Torres, Javier; Zorzano‐Mier, María‐Paz; Nyberg, Erik; Vakkada-Ramachandran, Abhilash; Bhardwaj, Anshuman
Abstract : Tribocorrosion is a degradation phenomenon of material surfaces subjected to the combined action of mechanical loading and corrosion attack caused by the environment. Although corrosive chemical species such as materials like chloride atoms, chlorides, and perchlorates have been detected on the Martian surface, there is a lack of studies of its impact on materials for landed spacecraft and structures that will support surface operations on Mars. Here, we present a series of experiments on the stainless-steel material of the ExoMars 2020 Rosalind Franklin rover wheels. We show how tribocorrosion induced by brines accelerates wear on the materials of the wheels. Our results do not compromise the nominal ExoMars mission but have implications for future long-term surface operations in support of future human exploration or extended robotic missions on Mars.